Education and Provision of Mung Bean and Purple Taro-Based Cookies as an Effort to Prevent Chronic Energy Deficiency in Pregnant Women - Novita Br Ginting Munthe; Iskandar Markus Sembiring (JURNAL PENGMAS KESTRA (JPK), 2026)
Chronic Energy Deficiency (CED) among pregnant women remains a significant nutritional problem that increases the risk of pregnancy complications, low birth weight, and stunting. Preventing CED requires improving pregnant women's knowledge of adequate nutritional intake during pregnancy and promoting the utilization of locally available food as supplementary nutrition. This community service program aimed to improve pregnant women's knowledge regarding the prevention of Chronic Energy Deficiency through health education and the provision of cookies made from mung bean (Vigna radiata) and purple taro (Colocasia esculenta). The program was conducted at Cahaya 2 Primary Clinic, Lubuk Pakam, Deli Serdang Regency, North Sumatra, in April 2026, involving 19 pregnant women diagnosed with CED. An educational-participatory approach was employed, consisting of health education sessions, interactive discussions, distribution of educational leaflets, provision of mung bean and purple taro cookies as supplementary food, and evaluation using pre-test and post-test questionnaires. The evaluation results demonstrated an improvement in participants' knowledge following the intervention. Before the educational session, most participants had a moderate level of knowledge (52.6%), while only 21.1% demonstrated good knowledge. Following the intervention, the proportion of participants with good knowledge increased to 89.5%, and no participants remained in the poor knowledge category. Product acceptability assessment showed that 94.7% of participants liked the taste and texture of the cookies, while all participants (100%) reported that the cookies were easy to consume as a supplementary food during pregnancy. These findings indicate that health education combined with the provision of locally sourced mung bean and purple taro cookies effectively improved pregnant women's knowledge regarding the prevention of Chronic Energy Deficiency and achieved high acceptability as an alternative supplementary food. Similar programs should be implemented continuously through antenatal care services to support improvements in maternal nutritional status and contribute to stunting prevention beginning during pregnancy.